Absorption and metabolism of modified mycotoxins of alternariol, alternariol monomethyl ether, and zearalenone in Caco‐2 cells. Issue 1 (2nd November 2020) - Appel (Kohn), Beate Nadine; Gottmann, Jörg; Schäfer, Judith; Bunzel, Mirko
Abstract: Background and objectives: Various cereals, fruits, and vegetables are commonly contaminated with mycotoxins such as zearalenone (ZEN), alternariol (AOH), and alternariol monomethyl ether (AME). More recently, their glucosidic metabolites formed in the plant have gained increasing attention. Experimental data on the contribution of modified mycotoxins to total toxicity are either controversy or lacking. Thus, the aim of this study was to investigate the absorption and metabolism of ZEN‐, AOH‐, and AME‐glucosides using the Caco‐2 cell system. Findings: No quantifiable amounts of ZEN‐14‐glucoside, ZEN‐16‐glucoside, free ZEN, and ZEN metabolites were found in Caco‐2 cells and in the basolateral compartment. In contrast, glucosides of AOH and AME were absorbed and released their parental toxins, which were further metabolized to form glucuronides and sulfates to a variable extent. Metabolites were found on the basolateral site, too. There is also evidence that AOH‐9‐diglucoside is hydrolyzed to AOH‐9‐glucoside. Conclusion: Our results demonstrate that modified ZEN is less absorbed whereas modified Alternaria toxins are taken up to a higher extent by Caco‐2 cells, followed by deglucosylation, metabolization, and transport to the basolateral site, suggesting a potential contribution to overall toxicity of these modified mycotoxins. Significance and novelty: For the first time, absorption studies using modified Alternaria toxins in the Caco‐2 cell system were carried out.